PENGARUH RASIO KEUANGAN TERHADAP PERUBAHAN LABA PADA PERUSAHAAN GARMENT YANG TERDAFTAR DI BEI (PERIDO 2015-2019) - Zahara Zahara; Kardi Kardi (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2022)
Profit is very important for a company, although profit cannot be ascertained. Profit changes can determine an increase or decrease in a company's financial performance. Financial ratios are very useful in a company and can also predict the company's financial condition in the future, so that it becomes a guide for investors to make decisions. The purpose of the study was to determine and examine the effect of financial ratios on changes in earnings. The study was conducted on garment manufacturing companies listed on the Indonesia Stock Exchange for the 2015-2019 period by taking a sample of 8 companies, using data before the pandemic period because data for 2020-2021 is not yet available. This study uses secondary data and selected by purposive sampling method. Multiple linear regression tests were used to examine hypotheses. The results of the study show that the Current Ratio (CR), Inventory Turn Over (ITO), Debt to Total Assets Ratio (DAR) and Net Profit Margin (NPM) have no significant effect on changes in profits in garment manufacturing companies listed on the IDX for the 2015-2019 period.